2019
DOI: 10.3390/ma12182964
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Modification of Ti13Zr13Nb Alloy on Adhesion of Antibiotic and Nanosilver-Loaded Bone Cement Coatings Dedicated for Application as Spacers

Abstract: Spacers, in terms of instruments used in revision surgery for the local treatment of postoperative infection, are usually made of metal rod covered by antibiotic-loaded bone cement. One of the main limitations of this temporary implant is the debonding effect of metal–bone cement interface, leading to aseptic loosening. Material selection, as well as surface treatment, should be evaluated in order to minimize the risk of fraction and improve the implant-cement fixation the appropriate manufacturing. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…The authors also evaluated the antibacterial properties of the prepared surfaces against S. aureus and AgNPs containing surfaces exhibited a distinct inhibition of bacterial growth, while the nanoparticle deficient surfaces showed minimal effect on bacterial growth. These results are in agreement with those observed by [18] and [19] which showed that modifying Ti specimen surfaces with nanosilver does not deteriorate the overall biocompatibility of the material construct while allowing for adequate antibacterial protection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The authors also evaluated the antibacterial properties of the prepared surfaces against S. aureus and AgNPs containing surfaces exhibited a distinct inhibition of bacterial growth, while the nanoparticle deficient surfaces showed minimal effect on bacterial growth. These results are in agreement with those observed by [18] and [19] which showed that modifying Ti specimen surfaces with nanosilver does not deteriorate the overall biocompatibility of the material construct while allowing for adequate antibacterial protection.…”
Section: Discussionsupporting
confidence: 92%
“…Applications of NPs in the selected research papers was mainly in the form of embedding the ultrafine structures into a coating material such as nanosilver-loaded bone cement coatings [18], nanosilver-loaded dopamine coatings [36], AgNP-filled hydrogen titanate nanotube layer [30], Ag nanoparticle-loaded TiO 2 nanorods (NRDs) coatings [32], hydroxyapatite (HA) coatings [34], thin mussel adhesive protein (Mefp-1)/AgNP composite film [24] and crosslinked gelatin/SG composite coating [20]. The incorporation of NPs into such surface modification coatings facilitates the slow release of ions from NPs and the subsequent reduction of toxicity and prolonged antibacterial effects.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of titanium biomaterials properties has been obtained by subjecting them to ion implantation [13,14], plating [15,16] and nitriding [17,18]. A popular method of obtaining better properties of the titanium alloys tested is coating them using silicates [19], chitosan [20,21], or phosphates including hydroxyapatite (HAp) [22][23][24][25] and nanoHAp [7,[26][27][28]-together with their composite combinations with other elements [26,[28][29][30][31][32][33]-thus facilitating better adhesion and antibacterial properties. Carbon and diamond-like coatings [34][35][36][37][38][39] and their composite combinations with other elements [40][41][42], as well as carbon nanotubes (CNTs) [41,[43][44][45] and their composite combinations with other elements [31,45,46] have been tested to obtain better mechanical (especially nanohardness) and anti-corrosive properties.…”
Section: Introductionmentioning
confidence: 99%
“…These results, among others, consist of improvement of mechanical properties, increase in their hardness and often improvement of their anti-corrosion properties. However, these positive changes are often accompanied by deterioration in surface quality, which is one of the disadvantages of laser surface modification techniques of most materials [17,23,33,44,[52][53][54]56,57,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Bone spacers are generally used during revision surgery to control postoperative infection as temporary implants [17]. Poly-methyl-methacrylate (PMMA) cement is the most known material used as a bone spacer [18].…”
Section: Implants In Use: the Case Of The Bone Spacersmentioning
confidence: 99%